Evaluation of Trichogramma spp. for the control of Trichoplusia ni - Milanez, André Malacarne; Pratissoli, Dirceu; Polanczyk, Ricardo Antonio; Bueno, Adeney de Freitas; Tufik, Camila Borges Antonio (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this study was to evaluate the biological characteristics of the parasitoids Trichogramma acacioi, T. atopovirilia, T. marandobai, T. demoraesi, T. exiguum (two lines), and T. pretiosum (six lines), reared on eggs of Trichoplusia ni. The experiment was carried out in a completely randomized design, with 15 replicates. The biological characteristics evaluated were: parasitism, viability, sexual ratio and number of individuals per egg. The parasitism percentage varied between 7.66 and 53%, whith highest value observed for Trichogramma pretiosum Tspd line, and the lowest for the T. pretiosum Trecife line. There was no significant difference for the viability, which remained higher than 85%. The sex ratio varied from 0.75 to 1, and Tspd line showed the lowest value. The number of individuals per egg varied between 2.39 for T. marandobai (Tm1 line) and 1.34 for T. exiguum (Te1 line). T. pretiosum (Tspd line) was the species with the best performance in laboratory with the highest values observed in parasitism and in viability.
Keywords: Brassicaceae; biological control; Cabbage looper; parasitism; egg parasitoids